Review--Within our Grasp: Childhood Malnutrition Worldwide and the Revolution Taking Place to End it - George Kent (World Nutrition, 2021)
Sharman Apt Russell’s book takes us on a tour of severe malnutrition worldwide and the responses to it. Her tour includes many side trips, helping readers to see the multifaceted nature of the problem.